2011
DOI: 10.1177/1534735411413269
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Hypothalamic–Pituitary–Thyroid Axis Function in Non-Small-Cell Lung Cancer Patients

Abstract: The aim of this study was to evaluate the hypothalamic-pituitary-thyroid (HPT) axis function in patients suffering from lung cancer. Thyrotropin-releasing hormone (TRH), thyroid-stimulating hormone (TSH), free thyroxine (FT4), interleukin (IL)-2, and melatonin serum levels were measured in blood samples collected every 4 hours for 24 hours from 11 healthy participants (H; ages 35-53 years) and 9 patients suffering from non-small-cell lung cancer (C; ages 43-63 years). Relationships between hormone levels overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Assessment of the pattern of HPT axis function in the setting of a 24 h sleep-wake schedule in 11 healthy participants (age of 35–53 years-old) and 9 patients with NSCLC (age of 43–63 years-old) by Mazzoccoli et al demonstrated that, compared to healthy participants, NSCLC patients had lower 24 h means TSH levels, but higher 24 h means TRH and fT4 levels. Nevertheless, both groups of patients experienced similar synchronization of the main body clock to the 24 h environmental light-dark cycle, resulting in a prominent circadian rhythm of TSH with peaks near midnight [ 102 ].…”
Section: Insights Into the Th–lung Cancer Association Gained Over The Last Three Decadesmentioning
confidence: 99%
“…Assessment of the pattern of HPT axis function in the setting of a 24 h sleep-wake schedule in 11 healthy participants (age of 35–53 years-old) and 9 patients with NSCLC (age of 43–63 years-old) by Mazzoccoli et al demonstrated that, compared to healthy participants, NSCLC patients had lower 24 h means TSH levels, but higher 24 h means TRH and fT4 levels. Nevertheless, both groups of patients experienced similar synchronization of the main body clock to the 24 h environmental light-dark cycle, resulting in a prominent circadian rhythm of TSH with peaks near midnight [ 102 ].…”
Section: Insights Into the Th–lung Cancer Association Gained Over The Last Three Decadesmentioning
confidence: 99%
“…The melatonin/cortisol mean nocturnal level ratio was also decreased in LC patients [75,76]. Taken together, these results suggested that lung cancer is associated with alteration in the proportions and 24-h profiles of various lymphocyte subsets; this may be related to disease stage and probably altered immune function [73][74][75]76].…”
Section: Circadian Biological and Behavioral Determinants In Lc Patiementioning
confidence: 73%
“…In LC patients, a progressive increase in GH and a steady decline of IGF-1 serum levels with loss of circadian rhythmicity were observed. This loss of diurnal rhythms could play a role in carcinogenesis and tumor growth regulation [71][72][73][74][75]. All profiles of time-related neuroendocrine-immune system components seemed to be the advancing stage of disease [71][72][73][74][75][76].…”
Section: Circadian Biological and Behavioral Determinants In Lc Patiementioning
confidence: 99%
“…They had the following common features: (1) middle age, smoking history and hypokalemia; (2) no significant clinical manifestations of Cushing’s syndrome, but increased ACTH and high level of cortisol in serum and urine; and (3) bronchoscopic biopsy confirmed SCLC. Changes in thyroid function in both patients were attributed to inhibition of the pituitary–thyroid axis by excess cortisol[16]. The condition of Patient 1 deteriorated rapidly, losing the best opportunity for treatment, whereas Patient 2 remained healthy for 2 years.…”
Section: Discussionmentioning
confidence: 99%